Answer: n = 6
Explanation:
The given equation is expressed as
-40+2n = 4n-8(n+8)
We would open the parenthesis on the right hand side of the equation by multiplying each term inside the parenthesis by the term outside. It becomes
- 40 + 2n = - 4n - 64
We would make all terms containing n to be on the left hand side of the equation and the constant terms to be on the right side of the equation. It becomes
2n - 6n = - 64 + 40
- 4n = - 24
Dividing the left hand side and the right hand side of the equation by
- 4, it becomes
- 4n/-4 = - 24/-4
n = 6